2016
DOI: 10.3389/fmicb.2016.00357
|View full text |Cite
|
Sign up to set email alerts
|

Dual Acting Neuraminidase Inhibitors Open New Opportunities to Disrupt the Lethal Synergism between Streptococcus pneumoniae and Influenza Virus

Abstract: Secondary infections with Streptococcus pneumoniae cause severe pneumonia and enhance lethality during influenza epidemics and pandemics. Structural and functional similarities with viral neuraminidase (NA) suggest that the highly prevalent pneumococcal NAs, NanA and NanB, might contribute to this lethal synergism by supporting viral replication and that dual acting NA inhibitors (NAIs) will disrupt it. To verify this hypothesis, NanA and NanB were expressed in E. coli. After confirming their activity in enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 46 publications
3
43
0
Order By: Relevance
“…There was no pre‐defined hypothesis or evidence for this increase, but its inclusion in the model was critical. This novel hypothesis subsequently guided several in vitro experimental studies, where at least two potential underlying mechanisms were discovered. First, S. aureus , another common coinfecting bacteria, was shown to inhibit IFN signaling in influenza‐infected cells, which resulted in increased virus production .…”
Section: Influenza‐bacteria Coinfection Kineticsmentioning
confidence: 91%
“…There was no pre‐defined hypothesis or evidence for this increase, but its inclusion in the model was critical. This novel hypothesis subsequently guided several in vitro experimental studies, where at least two potential underlying mechanisms were discovered. First, S. aureus , another common coinfecting bacteria, was shown to inhibit IFN signaling in influenza‐infected cells, which resulted in increased virus production .…”
Section: Influenza‐bacteria Coinfection Kineticsmentioning
confidence: 91%
“…Staphylococcus aureus , Streptococcus pneumoniae and Haemophilus influenzae are the major bacteria associated in simultaneous co-infection with influenza virus [2]. In vitro studies have shown that S. pneumoniae enhances influenza replication by producing a neuraminidase [3]. It has been suggested that it is difficult to evaluate the importance of viral/bacterial co-infection in the early years of an influenza pandemic due to low immunity.…”
mentioning
confidence: 99%
“…Moreover, results from previous studies showed that bacterial NA rescues influenza virus replication from inhibition by zanamivir328. In contrast, both 5 and 27 (50 µM) reduce the viral yield in A549 cells in the presence of NanA of DSM20566 from 100 to 31.8 ± 4.5% and 7.4 ± 1.2%.…”
Section: Resultsmentioning
confidence: 95%
“…The inhibition of the NA of whole 8178/09 and WSN/33 preparations and recombinant NanA of pneumococcus DSM205663 were studied. The readout was performed with a microplate reader (FLUOstar Omega, BMG Labtech GmbH, Ortenberg, Germany).…”
Section: Methodsmentioning
confidence: 99%